Analysis of oncological outcomes and renal function after laparoendoscopic single‐site (LESS) partial nephrectomy: a multi‐institutional outcome analysis. (25th November 2013) - Springer, Christopher; Greco, Francesco; Autorino, Riccardo; Rha, Koon H.; Derweesh, Ithaar; Cindolo, Luca; Richstone, Lee; Herrmann, Thomas R.W.; Liatsikos, Evangelos; Sun, Yinghao; Fanizza, Caterina; Nagele, Udo; et al.
Abstract : Objective: To report on a large multi‐institutional series of laparoendoscopic single‐site (LESS) partial nephrectomy (PN) and analyse renal function and short‐term oncological outcomes. Material and Methods: We conducted a retrospective analysis of consecutive cases of LESS‐PN performed between November 2007 and March 2012 at 11 participating institutions. Demographic data and data on the main peri‐operative outcomes and complications were gathered and analysed. Kidney function was evaluated by measuring serum creatinine concentration and estimated glomerular filtration rate (eGFR). Chronic kidney disease was defined in stages for each patient according to the National Kidney Foundation, Kidney Disease Outcomes Quality Initiative. Results: A total of 190 cases were included in this analysis. The mean renal tumour size was 2.6 cm, and the mean PADUA score was 7.2. The median operating time was 170 min with a median estimated blood loss of 150 mL. A clampless technique was used in 70 cases (36.8%) and the median warm ischaemia time (WIT) was 16.5 min. PADUA score independently predicted the length of WIT (low vs high score: odds ratio 5.11, CI 1.50–17.41, P = 0.009; intermediate vs high score: odds ratio 5.13, CI 1.56–16.88, P = 0.007). The overall postoperative complication rate was 14.7%. Where a clamping technique was used, a significant increase in serum creatinine concentration and a significant decrease in eGFR were observed postoperatively and at 6 months. On multivariate analysis PADUA score was the only predicting factor. Overall survival rates were 99, 97 and 88% at 12‐, 24‐ and 36‐month follow‐up, respectively, while disease‐free survival rates were 98% at 12‐month and 97% at 24‐ and 36‐month follow‐up. Conclusion: The study showed that LESS‐PN is effective in terms of renal function preservation and oncological control at short‐ and intermediate‐term follow‐up.